2014
DOI: 10.1016/j.neuropharm.2014.06.024
|View full text |Cite
|
Sign up to set email alerts
|

PPAR agonists regulate brain gene expression: Relationship to their effects on ethanol consumption

Abstract: Peroxisome proliferator-activated receptors (PPARs) are nuclear hormone receptors that act as ligand-activated transcription factors. Although prescribed for dyslipidemia and type-II diabetes, PPAR agonists also possess anti-addictive characteristics. PPAR agonists decrease ethanol consumption and reduce withdrawal severity and susceptibility to stress-induced relapse in rodents. However, the cellular and molecular mechanisms facilitating these properties have yet to be investigated. We tested three PPAR agoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
82
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 68 publications
(79 reference statements)
4
82
0
1
Order By: Relevance
“…PPARs are nuclear proteins that regulate gene expres sion and control neuroimmune responses and inflam mation [152]. Expression of PPARD (PPARδ subunit) and PPARGC1A (PPARγ coactivator) are altered in the basolateral and central amygdala of alcoholics [111], and PPAR agonists show promise in preclinical mod els of alcohol drinking, stressinduced relapse and withdrawal [153][154][155][156][157]. Because of the strong preclinical pharmacology and genetic data linking PPAR signal ing with alcohol intake, a clinical trial is currently underway to determine if the PPAR agonist fenofi brate will decrease craving for alcohol following cue exposure and reduce the number of drinks consumed in alcoholdependent subjects (ClinicalTrial.gov trial number: NCT02158273).…”
Section: Neuroimmune Signalingmentioning
confidence: 99%
“…PPARs are nuclear proteins that regulate gene expres sion and control neuroimmune responses and inflam mation [152]. Expression of PPARD (PPARδ subunit) and PPARGC1A (PPARγ coactivator) are altered in the basolateral and central amygdala of alcoholics [111], and PPAR agonists show promise in preclinical mod els of alcohol drinking, stressinduced relapse and withdrawal [153][154][155][156][157]. Because of the strong preclinical pharmacology and genetic data linking PPAR signal ing with alcohol intake, a clinical trial is currently underway to determine if the PPAR agonist fenofi brate will decrease craving for alcohol following cue exposure and reduce the number of drinks consumed in alcoholdependent subjects (ClinicalTrial.gov trial number: NCT02158273).…”
Section: Neuroimmune Signalingmentioning
confidence: 99%
“…One study, however, showed that clofibrate increased voluntary alcohol consumption in male spontaneous hypertensive rats, although a very high ethanol concentration was used (30% ethanol, v/v) (Schlicht, 1987). The PPARα agonist, fenofibrate, and the dual PPARα/γ agonist, tesaglitazar, selectively decreased voluntary alcohol consumption and preference in mice (Blednov et al, submitted; Ferguson et al, 2014). Gene expression profiling revealed that fenofibrate and tesaglitazar changed the transcriptome of mouse amygdala and prefrontal cortex (Ferguson et al, 2014), two important brain areas for reward and dependence.…”
Section: Peroxisome Proliferator-activated Receptors: Anti-inflammmentioning
confidence: 99%
“…The PPARα agonist, fenofibrate, and the dual PPARα/γ agonist, tesaglitazar, selectively decreased voluntary alcohol consumption and preference in mice (Blednov et al, submitted; Ferguson et al, 2014). Gene expression profiling revealed that fenofibrate and tesaglitazar changed the transcriptome of mouse amygdala and prefrontal cortex (Ferguson et al, 2014), two important brain areas for reward and dependence. The list of PPAR agonist-regulated genes was dominated by known neuronal genes, which was unexpected given the importance of glial cells (especially microglia) in regulating neuroimmune and inflammatory signaling in brain (Ferguson et al, 2014).…”
Section: Peroxisome Proliferator-activated Receptors: Anti-inflammmentioning
confidence: 99%
See 2 more Smart Citations